Functional and Morphological Parameters with Tissue Characterization of Cardiovascular Magnetic Imaging in Clinically Verified “Infarct-like Myocarditis” - Schwab, J.; Rogg, H.-J.; Pauschinger, M.; Fessele, K.; Bareiter, T.; Bär, I.; Loose, R. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: Cardiac magnetic resonance (CMR) has increasingly proved to be a valuable diagnostic tool for evaluating patients with suspected myocarditis. The objective of this study was to evaluate the diagnostic value of functional and morphological parameters including tissue characterization in patients with “infarct-like myocarditis”.Materials and Methods: 43 patients with clinically verified cases of “infarct-like myocarditis” (median time to MRI scanning after admission for acute symptoms 3 days) and 35 control patients matched by age and sex were included in this retrospective case control study. In this study we used a 1.5 T MRI scanner conducting steady-state-free-precession sequences, T2-weighted imaging, T1-weighted imaging before and after contrast administration and late gadolinium enhancement sequences. According to the recommendations for CMR diagnosis of myocarditis (Lake Louise consensus criteria), a scan was positive for acute myocarditis if 2 of 3 CMR criteria were present.Results: 30 % of the patients with “infarct-like myocarditis” had a reduced left ventricular ejection fraction, 11 % had an increased LV end-diastolic volume index and 35 % had an increased LV mass index. The sensitivity of wall motion abnormalities was 63 % with a regional distribution in 49 %. In 47 % of cases regional wall motion abnormalities were present in the lateral left ventricular segments. Pericardial effusions were discovered in 65 % of cases with a circular appearance in 21 % and focal manifestation in 44 %. The diagnostic sensitivity, specificity, and accuracy of CMR in patients with “infarct-like myocarditis” were 67 %, 100 % and 82 %, respectively. The LGE alone was the most sensitive test parameter with 86 %, providing a specificity of 100 % and accuracy of 92 %.Conclusion: Our study results can be applied to the subgroup of patients with “infarct-like myocarditis”, where we found that LGE alone was the most sensitive test parameter. In addition to tissue characterization, the functional and morphological analysis of patients with acute myocarditis provides a useful further diagnostic tool.Key Points:• Infarct-like myocarditis can be diagnosed by CMR with high validity and reliability.• LGE allone performed best with a sensitivity of 86 %. • Functional and morphological CMR parameters in addition to tissue characterization are useful tool in the diagnosis of acute myocarditis. Citation Format:• Schwab J, Rogg H-J, Pauschinger M et al. Functional and Morphological Parameters with Tissue Characterization of Cardiovascular Magnetic Imaging in Clinically Verified “Infarct-like Myocarditis”. Fortschr Röntgenstr 2016; 188: 365 – 373
Keywords: inflammation; heart; MR imaging